High Histamine Control Concentration Leads to False Negative Allergy Skin Testing - Amirneni, Amulya; Tversky, Jody (American journal of rhinology & allergy, 2021)
Allergy skin test reliability depends on the reagents and controls selected. Histamine is used at 1 mg/ml and 6 mg/ml concentration but few studies address the rationale for selecting one versus the other and how this may impact diagnostic accuracy. To determine the rate of false negative allergen skin tests responses between UniTest PC (using the 1 mg/mL histamine) and Quintip devices (using 6 mg/mL) for 4 common aeroallergens. Subjects aged 18-65 with symptoms of allergy to cat and/or ragweed received skin testing with 4 aeroallergens (dust mite mix, timothy grass, ragweed, cat), histamine and control diluent. Those individuals who tested positive to cat or ragweed with one skin prick test (SPT) device but not the other then proceeded to nasal allergen challenge (NAC). The primary outcomes were the aeroallergen false negative rates and sensitivities of the skin test devices followed by nasal allergen (NAC). Twenty-five individuals were recruited and underwent a total of 300 SPTs. SPT to allergens (ragweed, dust mite, cat, and timothy grass) resulted in a statistically significant difference in wheal size among the two skin testing devices ( value <0.0001, 0.0001, 0.0006, and 0.0053 respectively). Six NAC procedures were performed to cat/ragweed and 5 of 6 (83% were positive). The overall allergen sensitivity rate for UniTest and Quintip were 97% and 78% respectively with most false negatives due to the use of 6 mg/ml histamine control reagent. Our study shows that 6 mg/ml concentration of histamine control reagent may contribute to a false interpretation of aeroallergen skin prick test results.